The Effect of Transformational Leadership on Personnel Performance Through Work Spirit as an Intervening Variable (Study on Sampang Police Resort) - Chamariyah, Chamariyah; Ach. Ali Yafie; Rusdiyanto, Rusdiyanto (Sean Institute, 2025)
Ah. Ali Yafie, 2025. The Influence Of Transformational Leadership On Personnel Performance Through Work Spirit As An Intervening Variable (Study At Sampang Resort Police). Postgraduate Program, Wijaya Putra University, Surabaya. Based on its approach, this research is included in the explanatory research type. The research sample was 85 respondents. The objectives of this research are 1) To test and analyze the significant influence directly transformational leadership on the work spirit of Sampang Resort Police personnel ; 2) To test and analyze the significant influence directly transformational leadership towards performance of Sampang Resort Police personnel ; 3 To test and analyze the directly significant influence work enthusiasm towards the performance of Sampang Resort Police personnel ); 4) To test and analyze the influence of indirectly significant transformational leadership on personnel performance mediated by the work spirit of Sampang Resort Police personnel. The results of the study indicate that : 1) Transformational leadership has a significant positive effect on the work spirit of the Sampang Resort Police with an original sample value of 0.50; 2) Transformational leadership has a significant positive effect on the performance of Sampang Resort Police personnel with an original sample value of 0.350; 3) Work spirit has a significant positive effect on the performance of Sampang Resort Police personnel with an original sample value of 0.353; 4) Indirectly, transformational leadership has a significant effect on the performance of Sampang Resort Police personnel mediated by work spirit with an original sample value of 0.180.